Hyperbaric Oxygen Therapy for Suburethral Vaginal Mucosal Necrosis after Interstitial Irradiation for Recurrent Cervical Cancer. (10th September 2021) - Arakaki, Yoshihisa; Shimoji, Yuko; Nakasone, Tadaharu; Taira, Yusuke; Nakamoto, Tomoko; Kudaka, Wataru; Mekaru, Keiko; Aoki, Yoichi
Abstract : Patients with gynecological malignancies can develop radiation injuries, such as cystitis, proctitis, and soft tissue necrosis which have approved indications for hyperbaric oxygen therapy (HBOT). A 76-year-old Japanese woman with vaginal recurrence of cervical cancer was treated with the high-dose rate interstitial brachytherapy. Twenty-one months after the irradiation, she developed radiation necrosis on the external urethral opening. Two cycles of HBOT were performed. HBOT consisted of delivering 100% oxygen for 60 minutes at 2.4 atmospheres absolute. Pressure exposure was performed once daily, 5 days a week for 6 weeks. Eventually, the necrotic mucosa was completely replaced by the normal mucosa. No adverse effects were observed. We successfully treated a case of late adverse events of radiation therapy with HBOT. It was noninvasive and appears to be a useful treatment option which should be considered standard treatment practice.